Obstetric violence against abortion in a reference hospital in Vitória, ES, Brazil (Brazilian Journal of Health Research, 2023)
Introduction:This research is based on the need to discuss abortion, as it is a social and public health interest, and may be linked to some failures in care and guarantees of women’s rights. Objective: To analyze situations of obstetric violence related to abortion, based on the discourse of health professionals from a reference hospital in Vitória, ES. Methods: Thirteen health professionals who worked at the hospital during the collection period and who at some point directly participated in the provision of care to the person who experienced the abortion or after its complications, participated in the study. In-depth individual interviews were conducted based on the guiding question ‘Talk a little about what you think about abortion/abortion’ in order to explore the participants’ perceptions. For the interpretation and discussion of the findings, the Thematic Analysis derived from the Content Analysis was performed. Results: Data were organized into three major categories: 1. institutional violence; 2. negligent violence and 3. psychological violence. The reports demonstrate the presence of personal moral and religious principles intervening in care practices and that these often cross professional practices, contributing to the naturalization of often discriminatory attitudes. Conclusion: there is a gap between the recommendations found in the policies and ministerial documents and what is in fact guaranteed in the daily lives of women who access their rights related to abortion, with situations that characterize obstetric violence.
Keywords: Violence; Abortion; Women